The Effectiveness of the Job Loss Insurance Program (JKP) at the Employment Social Security Administration Agency in Padang City - Vivi Maida Sari; Yuliarti Yuliarti (Darul Yasin Al Sys, 2026)
Employment social protection and job loss insurance have become important issues in labor policy, yet research specifically addressing the effectiveness of the Job Loss Insurance Program (Jaminan Kehilangan Pekerjaan, JKP) at the local level remains limited. This study aims to analyze the effectiveness of the JKP program implemented by BPJS Ketenagakerjaan in Padang City. A descriptive qualitative approach was employed, involving JKP beneficiaries, BPJS Ketenagakerjaan officers, and a representative of the Department of Manpower and Industry of Padang City selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive model of Miles et al., consisting of data reduction, data display, and conclusion drawing or verification. The findings indicate that the JKP program has provided meaningful support for workers affected by termination of employment through cash assistance, access to labor market information, and job training opportunities. However, program effectiveness has not been fully optimized due to incomplete administrative documents, limited participant understanding, low digital literacy, limited human resources, uneven socialization, weak company compliance, and inconsistent inter-institutional coordination. These findings contribute to the development of program effectiveness analysis based on Campbell’s effectiveness indicators and extend current understanding of employment social security implementation at the local level. The study concludes that JKP plays an important role in supporting workers during the post-layoff transition period, but its effectiveness requires stronger administrative assistance, broader socialization, improved digital literacy support, enhanced company supervision, and more systematic coordination among BPJS Ketenagakerjaan, local government, and companies. Future research should examine the long-term impact of JKP on workers’ economic resilience and re-employment opportunities.